Removal of triclosan from aqueous solution using thermally treated rice husks - Triwiswara, Mutiara; Kang, Jin Kyu; Moon, Joon Kwan; Lee, Chang Gu; Park, Seong Jik (Desalination and Water Treatment, 2020)
This study investigated triclosan removal using rice husks thermally treated at 100°C, 300°C, and 500°C. Rice husks were characterized by analyzing their surface morphologies, pore size, pore diameter, specific surface area, elemental composition, and chemical functional groups. The rice husks thermally treated at 300°C (RH-300) displayed higher triclosan removal efficiency than those treated at other temperatures. Adsorption of triclosan onto RH-300 was achieved within 4 h, and the kinetic adsorption data were well described by a pseudo-first-order model. The Langmuir model described the equilibrium adsorption of triclosan to RH-300 more suitably than the Freundlich model did, indicating that triclosan was adsorbed on RH-300 as a monolayer. Positive enthalpy changes and negative free energy change obtained from thermodynamic experiments indicated that triclosan adsorption by RH-300 was endothermic and spontaneous under these experimental conditions. A decrease in triclosan adsorption with an increase in solution pH was more obvious in the RH-300 dosage of 3.33 than 6.67 g/L. As fulvic acid increased from 0–10 mg/L, triclosan adsorption onto RH-300 decreased by 25.3%; changes in triclosan adsorption were not distinct above 10 mg/L. In conclusion, RH-300 is a low-cost and effective material for the removal of triclosan from aqueous solutions.
Keywords: Adsorption; Pyrolysis; Rice husk; Thermal treatment; Triclosan